2018
DOI: 10.1371/journal.pone.0196067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of involvement of non-formal health providers on TB case notification among migrant slum-dwelling populations in Odisha, India

Abstract: BackgroundMigrant labourers living in the slums of urban and industrial patches across India make up a key sub-population so far controlling Tuberculosis (TB) in the country is concerned. This is because many TB patients from these communities- remain under reached by the Revised National Tuberculosis Control Programme (RNTCP) of India. This marginalized community usually seeks early-stage healthcare from “friendly neighbourhood” non-formal health providers (NFHPs). Because, RNTCP has limited capacity to invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Of these, more than half of the studies (62) were conducted at city level. The communicable diseases most frequently studied in the context of slums were diarrheal diseases (e.g., [54,55]), HIV (e.g., [56,57]), and tuberculosis (e.g., [58,59]), as expected. The communicable diseases are followed by studies on sexual and maternal behavior (13.6%).…”
Section: Analysis By Health Categoriessupporting
confidence: 70%
“…Of these, more than half of the studies (62) were conducted at city level. The communicable diseases most frequently studied in the context of slums were diarrheal diseases (e.g., [54,55]), HIV (e.g., [56,57]), and tuberculosis (e.g., [58,59]), as expected. The communicable diseases are followed by studies on sexual and maternal behavior (13.6%).…”
Section: Analysis By Health Categoriessupporting
confidence: 70%
“…Third, engagement of informal providers resulted in the identification of large numbers of PPTB, roughly constituting 7-8% of the TB patients detected in these TB Units [19]. The yield in the absolute number of PPTBs and TB cases was higher than a similar project conducted in Odisha State of India [20]. In the absence of this project, the 8342 PPTBs identified under this project either would have not been subjected to TB diagnostic evaluation or would have been subjected to diagnostic evaluation at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…This would have resulted in missed diagnosis or delayed diagnosis [ 21 ]. This would have increased the morbidity, mortality among these individuals, and the transmission of TB in the community, which was perhaps mitigated by the implementation of this project [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly featured IPs in TB care were Traditional Health Practitioners (THPs) (n = 8) [ 30 – 32 , 49 , 51 , 53 , 55 , 58 ], followed by traditional birth attendants (TBAs) (n = 3) [ 50 , 56 , 57 ] and drug sellers, storekeepers, and chemists (n = 3) [ 30 , 31 , 52 ]. The least featured IP type were untrained allopathic practitioners (n = 2) [ 30 , 54 ]. In all studies, IPs were given some training in TB before their involvement, but the duration varied.…”
Section: Resultsmentioning
confidence: 99%
“…A substantial body of research suggests that they are the first point of contact for a significant proportion of TB patients [ 27 , 28 ], but beyond that point, our understanding of their role in the prevention, diagnosis, and treatment of TB is limited. Studies which have explored the role of IPs in tuberculosis care have found that they create community awareness, assist in the diagnosis of symptomatic cases, and conduct sputum collection [ 30 – 32 ]. However, to our knowledge, their role has not been systematically explored using an evidence synthesis approach.…”
Section: Introductionmentioning
confidence: 99%